By using properties of determinants, show that:
$\left|\begin{array}{lll}1 & a & a^{2} \\ 1 & b & b^{2} \\ 1 & c & c^{2}\end{array}\right|=(a+b)(b-c)(c-a)$
Let $\Delta=\left|\begin{array}{lll}1 & a & a^{2} \\ 1 & b & b^{2} \\ 1 & c & c^{2}\end{array}\right|$
Applying $R_{1} \rightarrow R_{1}-R_{3}$ and $R_{2} \rightarrow R_{2}-R_{3},$ we have:
$\Delta=\left|\begin{array}{ccc}0 & a-c & a^{2}-c^{2} \\ 0 & b-c & b^{2}-c^{2} \\ 1 & c & c^{2}\end{array}\right|$
$=(c-a)(b-c)\left|\begin{array}{ccc}0 & -1 & -a-c \\ 0 & 1 & b+c \\ 1 & c & c^{2}\end{array}\right|$
Applying $R_{1} \rightarrow R_{1}+R_{2},$ we have:
$\Delta=(b-c)(c-a)\left|\begin{array}{ccc}0 & 0 & -a+b \\ 0 & 1 & b+c \\ 1 & c & c^{2}\end{array}\right|$
$=(a-b)(b-c)(c-a)\left|\begin{array}{ccc}0 & 0 & -1 \\ 0 & 1 & b+c \\ 1 & c & c^{2}\end{array}\right|$
Expanding along $\mathrm{C}_{1},$ we have:
$\Delta=(a-b)(b-c)(c-a)\left|\begin{array}{cc}0 & -1 \\ 1 & b+c\end{array}\right|=(a-b)(b-c)(c-a)$
Hence, the given result is proved.
Let $D_1 =$ $\left| {\,\begin{array}{*{20}{c}}a&b&{a + b}\\c&d&{c + d}\\a&b&{a - b}\end{array}\,} \right|$ and $D_2 =$ $\left| {\,\begin{array}{*{20}{c}}a&c&{a + c}\\b&d&{b + d}\\a&c&{a + b + c}\end{array}\,} \right|$ then the value of $\frac{{{D_1}}}{{{D_2}}}$ where $b \ne 0$ and $ad \ne bc$, is
If $\omega $is a cube root of unity, then $\left| {\,\begin{array}{*{20}{c}}{x + 1}&\omega &{{\omega ^2}}\\\omega &{x + {\omega ^2}}&1\\{{\omega ^2}}&1&{x + \omega }\end{array}\,} \right| = $
The determinant $\left| {\,\begin{array}{*{20}{c}}a&b&{a\alpha + b}\\b&c&{b\alpha + c}\\{a\alpha + b}&{b\alpha + c}&0\end{array}\,} \right| = 0$, if $a,b,c$ are in
By using properties of determinants, show that:
$\left|\begin{array}{ccc}x+y+2 z & x & y \\ z & y+z+2 x & y \\ z & x & z+x+2 y\end{array}\right|=2(x+y+z)^{3}$